Oral Feeding Outcome after Analgesic and Sedative Exposure in VLBW Preterm Infant - Astoria, Mark T.; Thacker, Leroy; Hendricks-Muñoz, Karen D. (American Journal of Perinatology, 2018)
Objective The objective of this study was to assess the association of analgesics and sedatives on oral feeding function and need for feeding tube at discharge in the very low birth weight (VLBW) (<1,500 g) preterm infant.Study Design A retrospective review of surviving inborn infants < 1,500 g and < 32 weeks' gestation (n = 209), discharged between January 1, 2012, and December 31, 2014, from the neonatal intensive care unit identified exposure to analgesic and sedative medications, demographics, medical course, and nasogastric or gastrostomy tube (GT) feeding at discharge. Predictive modeling with logistic regression to identify independent factors associated with discharge on tube feedings.Results Out of 209, 45 (21.5%) infants received an analgesic/sedative with 23 out of 45 (51.1%) discharged with tube feedings. Infants discharged with tube feedings were born smaller, of younger gestation, with greater SNAPPE-II scores, periventricular leukomalacia, chronic lung disease, postnatal glucocorticoids, lansoprazole, and longer time intubated. After adjusting for covariates, exposure to analgesic/sedatives (fentanyl, midazolam, or morphine) was independently predictive of discharge on tube feedings.Conclusion Analgesic and sedative exposure in VLBW infants is highly associated with poor oral feeding and need for tube feedings at discharge.
Keywords: premature infant; very low birth weight; sedation; analgesic; dysphagia